Jerry Jerome - Jerome, Jerry, 1912-2001; Rowe, Monk (Fillius Jazz Archive, Clinton, New York (DVD publisher); Transcoded for the Web by the Hamilton College Library., 1996)
Biography -- Childhood interest in drums/First lessons/Solfeggio was very strict -- Teaching himself saxaphone/First gigs -- Touring in depression/Joining Glenn Miller -- Glenn Miller : solos as part of arrangement -- Moving to Red Norvo -- Role of radio/Subbing for Lester Young on radio show -- Joining Benny Goodman -- Kansas City/Mary Lou Williams -- Sitting in with Basie/Work with Artie Shaw : "Stardust" recording/Playing society band gigs -- Writing beer jingle for Joe Williams -- Goodman, Basie anecdotes/Lester Young's bell -- Diagnosing Herschel Evans' illness. Tenor saxophonist Jerry Jerome was born in New York City in 1912. His first career choice was in medicine and he paid his medical school fees through gigs with the Clicquot Club Eskimos. Music eventually became his vocation and he played with the early Glenn Miller Orchestra in 1936 followed by work with Red Norvo, Benny Goodman, Lionel Hampton and Artie Shaw. Jerry has worked extensively in radio and television as a conductor, arranger and jingle writer and produced the Miller Beer commercial featuring the voice of Joe Williams. He performs in festivals and jazz concerts and is a favorite of the Sarasota Jazz Club. Date of interview: April 12, 1996; Date DVD created: c2003 Primary source material